A Localized surface plasmon resonance (LSPR) sensor integrated automated microfluidic system for multiplex inflammatory biomarker detection. Issue 23 (23rd September 2020) - Chen, Jhih-Siang; Chen, Pin-Fan; Lin, Hana Tzu-Han; Huang, Nien-Tsu
Abstract : We integrated an LSPR sensor with a single-layer four-channel microfluidic device operated via the automated microfluidic control system to realize multiplex inflammatory biomarker detection. Abstract : Inflammation is a complex biological response of the human body to external or internal stimuli, such as invading pathogens, defective cells, or irritating substances. One important indicator of inflammatory conditions or the progress of various diseases, such as cancer, cardiovascular diseases, neurological diseases, connective tissue diseases, sepsis, or Alzheimer's disease, is the concentration level of inflammatory biomarkers, including immunoglobulins, cytokines, and C-reactive protein (CRP). Since inflammatory biomarkers are highly correlated with each other, it is important to measure them simultaneously. To enable continuous and dynamic inflammatory biomarker detection, we utilized localized surface plasmon resonance (LSPR) to perform label-free molecule sensing. Since the LSPR sensing mechanism requires only a small sensing area with simplified optical setup, it can be easily integrated with a microfluidic device. To simplify reagent operation complexity, we developed an automated microfluidic control system to control reagent guiding and switching in the immunoassay with less manual processes and potential operation errors. Our results successfully demonstrated multiplex IgG, TNF-α, and CRP measurement with only 60 μL assay volume and 3.5 h assay time. In each test, 20 sensing spot measurements under four different reagent conditions can be performed. Overall, we envision that the LSPR sensor integrated automated microfluidic control system could perform rapid, multiplex, and multiparallel continuous inflammatory biomarker detection, which would be beneficial for various applications, such as immune status monitoring, diagnosis and prognosis of inflammatory diseases.